1973
DOI: 10.2134/agronj1973.00021962006500010014x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Row Width and Population Density on Yield and Fiber Characteristics of Cotton1

Abstract: A critical need to evaluate methods to reduce production costs of Upland cotton (Gossypium hirsutum L.) to help maintain its. competitive market position, prompted experiments designed to evaluate the influence of row width and plant population on yield and fiber properties. Upland cotton was grown in 25.4‐, 50.8‐, 76.2‐, and 101.6‐cm‐spaced rows with population levels of 128,000 (low) and 256,000 (high) plants/ha at three locations in Georgia. Significant differences in yield due to test location and to row w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 2 publications
0
20
0
3
Order By: Relevance
“…Maturity did not differ significantly between row spacings in the combined analysis across the six experiments (Tables 2 and 3). Other studies also report little difference in maturity between row spacings in cotton (Gerik et al, 1998; Hawkins and Peacock, 1973), while some report significantly earlier maturity (Cawley et al, 1998, 1999; Hearn and Hughes, 1975; Young et al, 1980), and others report inconsistent maturity differences between row spacings in different years of their studies (Constable, 1977b; Jost and Cothren, 2001). There was also no interaction of the application of mepiquat chloride and row spacing on maturity (Table 4), suggesting that the effect was consistent across spacing treatments.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Maturity did not differ significantly between row spacings in the combined analysis across the six experiments (Tables 2 and 3). Other studies also report little difference in maturity between row spacings in cotton (Gerik et al, 1998; Hawkins and Peacock, 1973), while some report significantly earlier maturity (Cawley et al, 1998, 1999; Hearn and Hughes, 1975; Young et al, 1980), and others report inconsistent maturity differences between row spacings in different years of their studies (Constable, 1977b; Jost and Cothren, 2001). There was also no interaction of the application of mepiquat chloride and row spacing on maturity (Table 4), suggesting that the effect was consistent across spacing treatments.…”
Section: Resultsmentioning
confidence: 96%
“…In low input systems differences in yield between row spacings have been variable with no consistent yield benefit with the use of UNR spacings. Some studies have reported higher yields in UNR crops (Atwell, 1996; Bader and Culpepper, 2002; Gerik et al, 1999, 1998, 2000; Gwathmey, 1996, 1998; Gwathmey et al, 1999; Hawkins and Peacock, 1973; Heitholt et al, 1992; Koli and Morrill, 1976; Nichols et al, 2003, 2004; Steglich et al, 2000; Vories et al, 2001), others have reported that differences in yield when comparing UNR and conventionally spaced cotton are not consistent across years (Bader and Culpepper, 2002; Cawley et al, 1998, 1999; Constable, 1977a, 1977b; Jost and Cothren, 2001; Nichols et al, 2004; Vories et al, 2001). There are studies that report no yield benefit in UNR cotton (Baker, 1976; Bednarz et al, 1999; Clawson and Cothren, 2002; Marois et al, 2004; Nichols et al, 2004), or yield was lower (Boquet.…”
Section: Resultsmentioning
confidence: 99%
“…Row spacing and plant density treatments did not affect micronaire readings in either year of the study (Table 9) These results are contrasted to those obtained by Vories et al (1999), who showed that in 2 out of 3 yr micronaire readings were reduced in UNRC vs. conventionally‐grown cotton. Results from past row spacing and plant density studies and their effect on micronaire have been varied (Douglas et al, 1970; Hawkins and Peacock, 1973).…”
Section: Resultsmentioning
confidence: 99%
“…Verificando-se a análise de variância para produção de algodão em caroço na Hawkins & Peacock (1970); Hawkins & Peacock (1973);Lamas (1988);Carmi (1996); Krieg (1996);Gerik et al (1998);Bednarz et al (1999);Gerik et al (1999). Contudo, Atwell et al (1996);Maas (1997);Bednarz et al (1999), obtiveram maior produção utilizando o espaçamento convencional.…”
Section: Produção De Algodão Em Caroçounclassified
“…Dentre as características tecnológicas da fibra, Williford (1992); Gwathmey Quanto ao índice micronaire, Hawkins & Peacock (1973) …”
Section: Características Tecnológicas Da Fibraunclassified